2020
DOI: 10.1111/dme.14277
|View full text |Cite
|
Sign up to set email alerts
|

The importance of hyperosmolarity in diabetic ketoacidosis

Abstract: Aim Diabetic ketoacidosis is a hyperglycaemic emergency that is often treated in intensive care units (ICUs) despite having a low mortality and good prognosis. Current risk stratification is based primarily on acidosis, but it has been suggested that hyperosmolarity may also be an important marker of increased severity. Our aim was to evaluate the relationship between raised serum osmolarity and adverse clinical outcomes in ICU admissions for ketoacidosis. Methods Retrospective review of prospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Measures of plasma osmolality, including crystal osmolality and colloid osmolality, which play important roles in regulating the distribution of water in blood vessels and inside and outside cells, are included in routine biochemical tests ( 2 ). Previous studies have shown that plasma osmolality is associated with the prognosis of patients with heart failure ( 3 , 4 ), myocardial infarction ( 5 , 6 ), and diabetic ketoacidosis ( 7 ), patients undergoing hemodialysis ( 8 ), elderly patients ( 9 ), and patients in the emergency room ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of plasma osmolality, including crystal osmolality and colloid osmolality, which play important roles in regulating the distribution of water in blood vessels and inside and outside cells, are included in routine biochemical tests ( 2 ). Previous studies have shown that plasma osmolality is associated with the prognosis of patients with heart failure ( 3 , 4 ), myocardial infarction ( 5 , 6 ), and diabetic ketoacidosis ( 7 ), patients undergoing hemodialysis ( 8 ), elderly patients ( 9 ), and patients in the emergency room ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance of osmolality is associated with increased risks of adverse clinical outcomes in adults and children in critical care. Prior studies have shown that plasma osmolality is correlated with the prognosis of patients with diabetic ketoacidosis and myocardial infarction, elderly hemodialysis patients, and emergency room patients (4)(5)(6)(7)(8). Plasma osmolality is also associated with a higher rate of mortality and adverse cardiac events in heart failure patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…Das Prinzip der neoadjuvanten Immuntherapie des fortgeschrittenen Melanoms sei aus seiner Sicht deshalb so spannend und aussichtsreich, weil bei der „perioperativen“ Therapie durch die größere Tumormasse mehr Neoantigene vorkommen und die immunologische Therapie besser wirken kann. Diese Verbesserung konnte mittlerweile als Proof-of-principle etwa mit einer Phase-I-Studie 1 oder der Phase-II-Studie SWOG S1801 2 auch klinisch gezeigt werden. Diese deutlich erkennbare Verbesserung des rezidivfreien Überlebens ist, so Mohr, „was wir für unsere Patienten wünschen“.…”
unclassified